2014
DOI: 10.1038/ncomms6260
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of breast cancer in Latinas identifies novel protective variants on 6q25

Abstract: The genetic contributions to breast cancer development among Latinas are not well understood. Here, we carry out a genome-wide association study of breast cancer in Latinas and identify a genome-wide significant risk variant, located 5’ of the Estrogen Receptor 1 gene (ESR1) (6q25 region). The minor allele for this variant is strongly protective (rs140068132: OR 0.60, 95%CI 0.53-0.67, P=9×10−18), originates from Indigenous Americans, and is uncorrelated with previously reported risk variants at 6q25. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 63 publications
3
123
1
1
Order By: Relevance
“…[20][21][22][23][24][25] Studies of admixed populations have been particularly fruitful in identifying genetic adaptations and risk for diseases that are stratified across diverged ancestral origins. [26][27][28][29][30][31] Admixture patterns became especially complex during the peopling of the Americas, with extensive recent admixture spanning multiple continents. Processes shaping structure in these admixed populations include sex-biased migration and admixture, isolationby-distance, differential drift in mainland versus island populations, and variable admixture timing.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] Studies of admixed populations have been particularly fruitful in identifying genetic adaptations and risk for diseases that are stratified across diverged ancestral origins. [26][27][28][29][30][31] Admixture patterns became especially complex during the peopling of the Americas, with extensive recent admixture spanning multiple continents. Processes shaping structure in these admixed populations include sex-biased migration and admixture, isolationby-distance, differential drift in mainland versus island populations, and variable admixture timing.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous American ancestry has consistently been associated with breast cancer risk, with lower risk among women with high Indigenous American ancestry (50,51). A genome-wide association study in Latinas reported the existence of a single nucleotide polymorphism, only present in Indigenous American populations, and associated with protection against breast cancer (52). In addition to this protective variant, non-genetic factors are likely to contribute to the decreased breast cancer risk in highly Indigenous American women, given that genetic ancestry is correlated with sociodemographic, reproductive and lifestyle factors such as education, neighborhood SES, use of HT and alcohol intake (53).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer Differences in Native American ancestry at the estrogen receptor locus led to discovery of a genetic variant that was protective against breast cancer in Latinas [11].…”
Section: Trait Findingsmentioning
confidence: 99%